2018
DOI: 10.1080/01443615.2018.1433647
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare provider advice on gestational weight gain: uncovering a need for more effective weight counselling

Abstract: Limited research has examined the factors related to knowledge of gestational weight gain (GWG) recommendations and the receipt of advice from healthcare providers regarding GWG recommendations among women with pre-pregnancy overweight/obesity. Women with pre-pregnancy overweight/obesity (N = 191) reported the amount of gestational weight they believed they should gain and that healthcare providers advised them to gain. Only 24% (n = 46) of women had a correct knowledge of GWG recommendations. Women were less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…This frequent counseling throughout gestation and also that women may be more receptive and motivated to make changes for their own and their babies health have suggested pregnancy to be a particular “teachable moment” ( ACOG, 2015 ). Still, and in line with the present results, qualitative research and surveys have shown that provider–patient communication regarding GWG, PA, and nutrition is infrequent and that, unless requested, few pregnant women receive regular guidance about these health topics ( de Jersey et al, 2012 , 2013 ; Stengel et al, 2012 ; Willcox et al, 2012 ; Whitaker et al, 2016 ; Morris et al, 2017 ; Wilkinson et al, 2017 ; Emery et al, 2018 ; McGee et al, 2018 ; Dalhaug and Haakstad, 2019 ). Hence, this evidence signals a lack of focus on lifestyle behavior in pregnancy and highlights the importance of improving healthcare provider’s knowledge, confidence, and skills in giving such guidance.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This frequent counseling throughout gestation and also that women may be more receptive and motivated to make changes for their own and their babies health have suggested pregnancy to be a particular “teachable moment” ( ACOG, 2015 ). Still, and in line with the present results, qualitative research and surveys have shown that provider–patient communication regarding GWG, PA, and nutrition is infrequent and that, unless requested, few pregnant women receive regular guidance about these health topics ( de Jersey et al, 2012 , 2013 ; Stengel et al, 2012 ; Willcox et al, 2012 ; Whitaker et al, 2016 ; Morris et al, 2017 ; Wilkinson et al, 2017 ; Emery et al, 2018 ; McGee et al, 2018 ; Dalhaug and Haakstad, 2019 ). Hence, this evidence signals a lack of focus on lifestyle behavior in pregnancy and highlights the importance of improving healthcare provider’s knowledge, confidence, and skills in giving such guidance.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, this evidence signals a lack of focus on lifestyle behavior in pregnancy and highlights the importance of improving healthcare provider's knowledge, confidence, and skills in giving such guidance. On the other side, most of the studies regarding prevalence of prenatal lifestyle counseling are based on the pregnant women's report of provider advice (Stengel et al, 2012;Whitaker et al, 2016;Emery et al, 2018;Dalhaug and Haakstad, 2019), and some have shown little congruence between patient and healthcare providers perceptions of counseling practice (Lutsiv et al, 2012;Ferraro et al, 2013). This discrepancy may be due to the healthcare providers giving socially desirable responses or the pregnant women not recalling having received advice from their healthcare provider.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional limitation is that this study was limited to a highly educated, predominately white population who were largely recruited from a breastfeeding support website, which limits generalizability. Previous studies examining provider advice and GWG in singleton pregnancies have been conducted in predominately white populations [20,21,23,32,33,[39][40][41][42], as done for the present study, with several exceptions where the majority of participants were Hispanic or African American women [19,22,[43][44][45]. It is also known that women with twins are less likely to initiate breastfeeding compared to women with singletons [46]; thus it is important to acknowledge that the population in the present study is unique as they were largely recruited from a breastfeeding support group.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, pregnant women regard the prenatal healthcare advice from their healthcare providers as reliable and credible [ 22 , 23 , 24 ], and they may feel motivated to make lifestyle changes; and in this case, prenatal physical activity practice for healthy pregnancy and birth, it would be beneficial. Notably, the majority of studies on prenatal physical activity counselling are based on women’s reports of prenatal care provider advice and counselling [ 23 , 25 , 26 , 27 , 28 , 29 ]. Therefore, the synthetization of evidence on this particular topic from the perspective of the prenatal care providers may serve to inform a best practice model on prenatal physical activity advice and counselling for prenatal healthcare providers working in primary antenatal healthcare services.…”
Section: Introductionmentioning
confidence: 99%